School Feeding Program in Nigeria: Ethical Issues (International Journal of Scientific Research and Management (IJSRM), 2025)
In Nigeria, the National Home-Grown School Feeding Program (NHGSFP) has the potential to support regional agricultural economies and give pupils wholesome meals. Nonetheless, a careful examination is necessary due to worries about its operational effectiveness and ethical purity. This study assesses how the NHGSFP affects academic achievement, school attendance, and community involvement. The study examines claims of misconduct and corruption in the program and suggests methods to improve ethics. The study’s conclusions provide insight into how views of the NHGSFP are correlated with demographic patterns, including age, occupation, community type, state of residence, and education level. Using a mixed-methods approach, this study looked at corruption claims and ethical issues inside the NHGSFP in addition to quantitatively analyzing survey data. A sample of respondents spanning a range of variables, including age, gender, education level, community type, state of residence, and occupation, were given a structured questionnaire. The questionnaire was designed to obtain complete data on participants’ opinions and experiences linked to the NHGSFP. Using SPSS software, data analysis was done to evaluate the program’s impact, demographic trends, and perceptions of corruption claims. Descriptive statistics, regression analysis, chi-square testing, and correlation analysis were used to investigate correlations between variables. The analysis highlights the influence of education on opinion formation by showing that respondents with greater levels of education often had more positive evaluations of the NHGSFP’s impact. Furthermore, compared to their rural counterparts, urban dwellers typically express more positive opinions, suggesting regional differences in program perception. Additionally, the NHGSFP is more well-liked by responders from some states than others, highlighting the necessity of individualized interventions based on regional context. Occupational analysis highlights the variety of viewpoints held by stakeholders, underscoring the significance of focused communication tactics. It’s interesting to see that believing in the program’s beneficial impact is correlated with being aware of corruption claims; this suggests a complex link that needs more investigation. To prevent corruption within the NHGSFP, the study suggests strong financial controls, ethics training, and open procurement procedures. In addition, it promotes streamlined enrolment processes and improved information sharing to guarantee fair access to the program’s advantages. These results offer insightful information to stakeholders and policymakers, supporting evidence-based decision-making and the moral development of the NHGSFP to better serve communities and learners in Nigeria.